The prevalence of food allergy in cesarean-born children aged 0–3 years: A systematic review and meta-analysis of cohort studies - Yang, Xiaoxian; Zhou, Chuhui; Guo, Chentao; Wang, Jie; Chen, Innie; Wen, Shi Wu; Krewski, Daniel; Yue, Liqun; Xie, Ri-hua (Frontiers in Pediatrics, 2023)
Purpose: Previous studies reported higher risk of food allergy for cesarean-born children than vaginal-born children. This study aimed to systematically compare the prevalence of food allergy among cesarean-born and vaginal-born children aged 0-3 years. Methods: Three English and two Chinese databases were searched using terms related to food allergy and cesarean section. Cohort studies that reported the prevalence of food allergy in cesarean-born and vaginal-born children aged 0-3 years were included. Two reviewers performed study selection, quality assessment, and data extraction. The pooled prevalence of food allergy in cesarean-born and vaginal-born children was compared by meta-analysis. Results: Nine eligible studies, with 9,650 cesarean-born children and 20,418 vaginal-born children aged 0-3 years were included. Of them, 645 cesarean-born children and 991 vaginal-born children were identified with food allergy. The pooled prevalence of food allergy was higher in cesarean-born children (7.8%) than in vaginal-born children (5.9%). Cesarean section was associated with an increased risk of food allergy (OR 1.45; 95% CI: 1.03-2.05) and cow’s milk allergy (OR 3.31; 95% CI: 1.98-5.53). Additionally, cesarean-born children with a parental history of allergy had an increased risk of food allergy (OR 2.60; 95% CI:1.28-5.27). Conclusion: This study suggests that cesarean section was associated with an increased risk of food and cow’s milk allergy in children aged 0-3 years. Cesarean-born children with a parental history of allergy demonstrated a higher risk for food allergy than did vaginal-born children. These results indicate that caregivers should be aware of the risks of food allergy in cesarean-born children, reducing the risk of potentially fatal allergic events. Further research is needed to identify the specific factors affecting food allergy in young children.